Archaeological crop marks detection through drone multispectral remote sensing and vegetation indices: A new approach tested on the Italian pre-Roman city of Veii. (February 2022) - Materazzi, Filippo; Pacifici, Marco
Abstract: The use of drones for archaeological research has been increasing rapidly in recent years, as can be seen in the large number of studies mentioning their use. Nonetheless, few of these studies focus on the identification of archaeological marks, and even fewer are based on multispectral imaging. This study demonstrates how drone multispectral remote sensing combined with an agronomic approach can guarantee great improvements in the identification of crop marks, opening up opportunities from both an economic and scientific point of view. An innovative multispectral camera makes it possible to record the vegetation reflectance in four different bands of the electromagnetic spectrum, including the near infrared spectrum, which is the most important band for vegetation analysis. The aerial imagery was processed using vegetation indices to identify crop marks, through the analysis of the type and variations of vegetation stress produced by buried remains. The experimental application of this technique on a portion of the Etruscan city of Veii demonstrates how, even in a single flight that was undertaken slightly later than the ideal timing, it was possible to detect and interpret a considerable amount of particularly significant archaeological marks.